The Information System of Detecting the Informed Activities in Derivative Asset Tradings; The 9th International Forum on Strategic Techology (IFOST-2014), September 21-23, 2014, Cox's Bazar, Bangladesh - Kritski O. L. Oleg Leonidovich (Information & Communication Technology, 2014)
Title screen